[History] - Charan, Minu Sinha (Golden, 2016)
1. Bricks, beads and bones - The Harappan Civilisation -- 2. Kings, farmers and towns - Early states and economies (C. 600 BCE-600 CE) -- 3. Kingship, caste and class - Early societies (C. 600 BCE-600 CE) -- 4. Thinkers, beliefs and buildings - cultural developments (C. 600 BCE-600 CE) -- 5. Through the eyes of travellers - Perceptions of society (C. Tenth of Seventeenth Centuries) -- 6. Bhakti-Sufi traditions - Changes in religious beliefs and devotional texts (C. Eighth to Eighteenth Centuries) -- 7. An imperial capital: Vijayanagara (C. Fourteenth to Sixteenth Centuries) -- 8. Peasants, Zamindars and the state - Agrarian society and the Mughal Empire (C. Sixteenth-Seventeenth Centuries) -- 9. Kings and chronicles : The Mughal Courts (C. Sixteenth-Seventeenth Centuries) -- 10. Colonialism and the countryside exploring (Official archives) -- 11. Rebels and the Raj - The revolt of 1857 and its representations -- 12. Colonial cities - Urbanisation, planning and architecture -- 13. Mahatma Gandhi and the Nationalist Movement - Civil disobedience and beyond -- 14. Understanding partition - Politics, memories, experiences -- 15. Framing of the constitution - The beginning of a new era